AN INTEGER LINEAR PROGRAMMING APPROACH APPLIED TO THE CERRADO (SAVANNA) MANAGEMENT - Haddad, Henrique Moreira Dabien; Gomide, Lucas Rezende; Cruz, Bruno Rogério; da Silva, Sérgio Teixeira (Floresta, 2014)
Abstract Cerrado presents great potential for the use of its resources, whether timber or non-timber, as fruits, firewood and charcoal. Thus, this study aimed to test the use of forest regulation model type I in a remnant of cerrado, applying the integer linear programming. The studied area was a remnant of cerrado sensu stricto located in São Romão – MG. The type of forest management carried out was the strip cutting. with post regeneration conduction. The model type I was applied generating 8 scenarios considering 14 years of planning horizon. The tested scenarios considered the area control, volume control and also both controls in the same model, where the objective function was to maximize the present value of revenues (PVR). After data processing it was observed that scenario 5 was the best, because it obtained the lowest amplitude variation (425 – 575 ha/year) and volume (18.000 – 21.000 m3/year) of the exploited surface limits, presenting a PVR of R4,004,561.58. It is possible to conclude that the developed models were able to regulate the volumetric yield in constant flows over the planning horizon, representing a promising alternative for the sustainable planning of the wood resources of the cerrado. Keywords: Mathematical programming; forest regulation; forest management. Resumo Uma abordagem aplicada da programação linear inteira no manejo do cerrado. O cerrado apresenta um grande potencial de uso de seus recursos, sejam eles madeireiros ou não madeireiros, como frutos, lenha e carvão vegetal. Assim, o trabalho teve como objetivo testar o uso do modelo tipo I de regulação florestal em um remanescente de cerrado utilizando a programação linear inteira. A área de estudo foi um remanescente de cerrado sensu stricto localizado em São Romão – MG. O regime de manejo elaborado foi o corte em faixas com posterior condução da regeneração. O modelo tipo I foi aplicado gerando 8 cenários em um horizonte de planejamento de 14 anos. Os cenários testados consideraram o controle por área, por volume, bem como ambos no mesmo modelo, sendo a função objetivo o valor presente das receitas (VPR) a ser maximizado. Após o processamento dos modelos observou-se que o cenário 5 foi o melhor, possuindo limites de área explorada (425 – 575 ha/ano) e volumétricos (18.000 – 21.000 m3/ano) com menor variação de amplitude, apresentando R4.004.561,58 de VPR. Pôde-se concluir que os modelos formulados foram capazes de regular a produção volumétrica em fluxos constantes ao longo do horizonte de planejamento, em sua grande maioria, constituindo-se de uma alternativa promissora ao planejamento sustentável dos recursos madeireiros do cerrado. Palavras-chave: Programação matemática; regulação florestal; manejo florestal.